CARbodies: Human Antibodies Against Cell Surface Tumor Antigens Selected From Repertoires Displayed on T Cell Chimeric Antigen Receptors - Vanesa Alonso-Camino; David Sánchez-Martín; Marta Compte; Natalia Nuñez-Prado; Rosa M Diaz; Richard Vile; Luis Alvarez-Vallina (Elsevier, 2013)
A human single-chain variable fragment (scFv) antibody library was expressed on the surface of human T cells after transduction with lentiviral vectors (LVs). The repertoire was fused to a first-generation T cell receptor ζ (TCRζ)-based chimeric antigen receptor (CAR). We used this library to isolate antibodies termed CARbodies that recognize antigens expressed on the tumor cell surface in a proof-of-principle system. After three rounds of activation-selection there was a clear repertoire restriction, with the emergence dominant clones. The CARbodies were purified from bacterial cultures as soluble and active proteins. Furthermore, to validate its potential application for adoptive cell therapy, human T cells were transduced with a LV encoding a second-generation costimulatory CAR (CARv2) bearing the selected CARbodies. Transduced human primary T cells expressed significant levels of the CARbodies-based CARv2 fusion protein on the cell surface, and importantly could be specifically activated, after stimulation with tumor cells. This approach is a promising tool for the generation of antibodies fully adapted to the display format (CAR) and the selection context (cell synapse), which could extend the scope of current adoptive cell therapy strategies with CAR-redirected T cells.